Role of total polyphenol content in seed germination characteristics of spring barley varieties amidst climate change - Ivana Jovanović; Nicole Frantová; Jhonny E. Alba-Mejía; Lenka Porčová; Vratislav Psota; Jana Asszonyi; Radim Cerkal; Tomáš Středa (Scientific Reports)
Abstract The amount of total polyphenol content (TPC) in the grain could provide insights into the conditions during maturation and might also serve as an indicator of the grain’s ability to germinate in the malting process or as seeds in the field. Varieties with higher natural TPC content might exhibit better germination parameters both in the field and in the malt house. This study investigates the relationship between TPC and seed germination characteristics i.e. seed vigour in four spring barley varieties over two years, considering diverse environmental conditions and exposure to drought conditions. The evaluation of seed germination characteristics in barley, with a focus on the root length and average diameter under drought conditions (−0.5 MPa) and suboptimal temperature (10 °C), was conducted. Drought conditions were induced using polyethylene glycol (PEG 6000). After durations of seven and fourteen days, the germinated seeds from the Petri dishes were scanned and subjected to analysis using WinRHIZO software following the metrics: Len 7, Len 14 (root length after seven and fourteen days in cm) and AvgD 7, AvgD 14 (root diameter after seven and fourteen days in mm). The findings support our initial hypothesis, indicating a variety-specific relationship between seed germination characteristics and increased TPC, where higher germination parameters might be associated with elevated TPC levels in some barley varieties.